Is there publication selection bias in minimum wage research during the five-year period from 2010 to 2014? - Georgios Giotis; Michael Chletsos (Kiel Institute for the World Economy (IfW), 2015)
The impact of minimum wages on employment has always been a field of conflicts among economists and this divergence of views has usually taken the form of competing studies. Doucouliagos and Stanley (Publication selection bias in minimum-wage research? A meta-regression analysis, 2009) conducted a meta-analysis of 64 US studies which showed that literature is contaminated by publication selection bias, and once it is corrected, little or no evidence of a negative association between minimum wages and employment remains. This result contradicts the neoclassical theory and gives a Keynesian perspective which suggests that changes in minimum wages are not related with positive or negative employment effects. In their analysis, the authors use a meta-sample of 45 empirical studies published in academic journals in the 2010-2014 five-year period, to investigate whether minimum wage research has been affected by Doucouliagos and Stanley's study. Their results indicate that there is evidence of publication selection in the elasticities' meta-sample, but once it is corrected only a small negative effect remains and, in the coefficients' meta-sample, publication selection bias is not found and the genuine effect is again negative but small. In addition, the authors find that study characteristics related to the data, the model specifications, the minimum wage and employment measure used, and the industry concerned, diversify the sign of the minimum wage effect.
http://dx.doi.org/10.7910/DVN/X2AZEJ
Keywords: J38; J21; C12; 330; minimum wage; employment; meta-analysis